Chemotherapy for advanced HER2-negative breast cancer: Can one algorithm fit all?. (November 2017) - Miglietta, F.; Dieci, M.V.; Griguolo, G.; Guarneri, V.; Conte, P.F.
Highlights: HER2-negative (HER2-) metastatic breast cancer (MBC) represents a biologically and clinically heterogeneous disease. Chemotherapy is an important element of the treatment armamentarium for HER2-MBC. To date, there is not a univoque algorithm capable of guiding the choice of the proper CT sequence. Results from prospective trials and meta-analysis suggest that specific subsets of patients could preferentially benefit from particular CT agents. The decision making process should be conducted on a patient-by-patient basis. Abstract: HER2negative (HER2-) metastatic breast cancer (MBC) represents a challenging scenario for clinicians due to its great biological and clinical heterogeneity. Although management of HER2-MBC currently relies on several options, CT still remains a worthwhile strategy to be exploited. However, to date, there is not an univoque algorithm capable of guiding the choice of the proper CT agent/regimen, sequence and duration. Evidence from randomized clinical trials (RCT) and meta-analyses can actually help guiding the decision making process, however the definition of a standard of care for all HER2-MBC patients may be impractical, also in the light of the identification of new promising molecular and immunotherapeutic agents. The purpose of this work is to review available evidence on the role of CT for HER2-MBC with particular emphasis on the need to outline personalized therapeutic strategies for each patient.